CLASSIFICATION OF MOTOR IMAGERY BASED ELECTROENCEPHALOGRAPHIC BRAIN COMPUTER INTERFACE USING BRAIN CONNECTIVITY - AWAIS, MUHAMMAD AHSAN (2021)
Motor imagery-based brain-computer interfaces have gained much attention in the past few years. It enables the ability to control external devices, such as prosthetic arms and wheelchairs, using brain activities. Several studies discuss the occurrence of MI actuated signals in primary sensorimotor areas. In contrast, other researchers report the inter-communication of multiple brain regions during motor tasks, thus making it difficult to isolate one or two brain regions where the motor activity takes place. Therefore, a deeper understanding of the behavior of brain neural patterns is important for BCIs to provide more useful and insightful features. Since the execution of motor or cognitive task results in the information exchange of multiple mutually interconnected brain regions.